2022
DOI: 10.32479/ijeep.11941
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Energy Efficiency of Higher Educational Buildings: A Case Study Approach

Abstract: Previous studies have reported that buildings consume nearly 36% of the total energy used and contribute towards 30% of the total carbon dioxide (CO2) emissions. Therefore, improving energy efficiency in buildings is essential to enhance a sustainable built environment. This research employed a case study approach with the Universiti Tun Hussein Onn Malaysia (UTHM) being selected as the case study. A number of buildings recorded high annual energy consumption (EC) data while others recorded low energy consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They reported that buildings utilized mostly for research had the greatest annual energy use intensity (EUI) value, coming in at 216 kWh/m 2 , while academic office buildings had the lowest value, coming in at 137 kWh/m 2 . Mohd Shukri et al (2022) researched energy use at Universiti Tun Hussein Onn Malaysia to generate an EE standard for higher education structures. The standard practicable range, according to statistical research, was between 72.5 and 141.0 kWh/m 2 /year.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They reported that buildings utilized mostly for research had the greatest annual energy use intensity (EUI) value, coming in at 216 kWh/m 2 , while academic office buildings had the lowest value, coming in at 137 kWh/m 2 . Mohd Shukri et al (2022) researched energy use at Universiti Tun Hussein Onn Malaysia to generate an EE standard for higher education structures. The standard practicable range, according to statistical research, was between 72.5 and 141.0 kWh/m 2 /year.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The energy pattern used every time EIS generates, and the usage schedule of each room becomes the basis for energy conservation. [16] According to Motegi et al [21], EIS is one element of the framework of the energy management and control system (EMCS), which is divided into four stages:…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study of energy consumption by Mukhametshin et al [15] in the regions of the Russian Federation also had been conducted using comparative analysis and evaluation to identify problems in the supply of their energy resource. A study also uses statistical analysis to develop an energy efficiency benchmark for university buildings Universiti Tun Hussein Onn Malaysia (UTHM) by Mohd Shukri et al [16]. Web technology that Internet media can access can facilitate the implementation of transparent monitoring of electrical energy consumption [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, green school building and non-green school buildings have been compared using statistics and analysis of variance (ANOVA) to determine whether there is a significant difference, and the results revealed that green school buildings consumed 32% less energy compared with non-green school buildings [35]. Another study employed statistics to develop an energy efficiency benchmark using a case study approach, and found that university buildings with an energy consumption of 72.5 kWh/m 2 /year can be considered as an energy-efficient building [36]. In addition, the energy consumption of green public buildings has been evaluated, and G-SEED certified and G-SEED non-certified public buildings have been analyzed using comparative analysis based on data from an open public portal, and the results revealed that the energy consumption intensity of G-SEED certified public buildings was 35.5-48.9% lower than that of the non-certified counterparts [37].…”
Section: Previous Studies On the Energy Consumption Analysis Of Publi...mentioning
confidence: 99%